Opinion 2394: Conus antidiluvianus Bruguière, 1792: prevailing usage of specific name conserved by setting aside the unidentifiable lectotype and replacing it with a neotype (Mollusca, Gastropoda, Conidae) - ICZN (Bulletin of Zoological Nomenclature, 2017)
The International Commission on Zoological Nomenclature has used its plenary power to conserve the specific name for the fossil cone shell Conus antidiluvianus Bruguière, 1792 by designating a neotype. The name is placed on the Official List of Specific Names in Zoology.
Keywords: Nomenclature; taxonomy; CONIDAE; Conus antidiluvianus; Conus parisiensis; Paris Basin; Italy; fossil cone shells